Effect of Powder/Liquid Ratio on Fluoride Release of Glass Ionomers - Torabzadeh, Hassan; Ghassemi, Amir; Janani, Anoosheh; Raoofinejad, Fatemeh; Naderi, Hani; Akbarzadeh Bagheban, Alireza (Journal of Dental School, 2019)
Objective: Evidence shows that the powder/liquid mixing ratio recommended by the manufacturers is often not respected when mixing the glass ionomer (GI) powder and liquid, yielding a GI cement with disproportionate powder/liquid ratio. Considering the confirmed effect of powder/liquid ratio on the GI properties, and more importantly, its fluoride release potential, this study aimed to assess the effect of powder/liquid ratio on fluoride release of GI cements. Methods: Fuji II, Fuji II LC Improved and Fuji IX GI cements were used in this experimental study. Of each material, three groups with powder 20% less than recommended, the exact recommended ratio and powder 20% more than recommended, were prepared. To assess the fluoride release potential, 45 disc-shaped specimens measuring 2×4mm were prepared (5 per each group). After fabrication, the specimens were immersed in 5 mL of distilled water. The amount of fluoride released into distilled water was measured at days 1 to 7, and also at 13, 14, 15, 28, 29, 30, 58, 59, 60, 88, 89, and 90 days, using Ion Selective Electrode (ISE). After each time of measurement, distilled water was replaced. Data were analyzed using repeated measures ANOVA. Tukey’s post hoc test was used for pairwise comparison of groups and powder/liquid mixing ratio. For pairwise comparison of time points, the Bonferroni adjustment was applied (p<0.05). Results: Based on the results, although the amount of fluoride released from Fuji IX was higher than Fuji II, this difference was not statistically significant (p=0.589). The lowest fluoride release was seen in Fuji II LC and this difference was statistically significant (p<0.05). Change by 20% in the powder/liquid mixing ratio in the three GI cements had no significant effect on fluoride release (p=0.650, p=0.103, p=0.082). Conclusion: Fluoride release from GI was time-dependent and the amount of released fluoride decreased over time. Fuji II LC resin-modified GI (RMGI) released less fluoride than Fuji II and Fuji IX. Also, 20% change in powder/liquid mixing ratio had no significant effect on fluoride release in different groups.